Determination of Phytochemical Compounds (Tannins, Saponins and Flavonoids) as Quercetin In Inggu Leaf Extract (Ruta angustifolia L.) - Shafa Noer; Rosa Dewi Pratiwi; Efri Gresinta (EKSAKTA: Journal of Sciences and Data Analysis, 2018)
Empirically, Inggu leaves (Ruta angustifolia L.) has potential to be used as raw material of traditional medicine because it contains phytochemical substances. The main organ most widely used as a traditional medicine is its leaves. Phytochemical compounds contained in the leaves of inggu include quercetin, tannin and saponins. Quercetin is a class of flavonol compounds (part of flavonoids). Quercetin has the ability to prevent the oxidation process from low density lipoprotein (LDL) by capturing free radicals and inhibiting transition metals, so that quercetin is believed to protect the body from various degerative diseases. While flavonoids are compounds consisting of 15 carbon atoms thatact as plant pigments. The function of flavonoids is to protect the cell structure, increase the effectiveness of vitamin C, antiinflammatory and as an antibiotic. While saponin and tannin are a group of active compounds of plants that have a sense of bitter and have antibacterial activity. This study was aim to determine the number of quercetin, tannins and saponins contained in the inggu’s leaves. Preparation of inggu leaf sample was done by maceration extraction technique used 96% ethanol solvent. Analysis of tannin and quercetin levels was determined by UV-Visible Spectrophotometry at 725 nm wavelength (λ).While the analysis of saponin content using TLC Scanner at 301 nm wavelength (λ). The results showed that content of quercetin was 1.67%; saponins 2.13% and tannins 7.04%.